2022
DOI: 10.1108/ijes-12-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Is trade, energy consumption and economic growth threat to environmental quality in Bahrain–evidence from VECM and ARDL bound test approach

Abstract: PurposeThe Kingdom of Bahrain has had tremendous development in various areas in the last decade. As a result of this, increasing energy consumption in Bahrain puts a strain on the country's energy supplies and increased CO2 emissions. This study investigates the determinants of carbon emissions in Bahrain.Design/methodology/approachThis study employs the autoregressive distributed lag (ARDL) bounds test and vector error correction model (VECM) Granger causality cointegration methods for empirical analysis dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Studies prove a strong positive connection between business and the overall environment. As FDI is more inclined toward investment in less efficient entry and exit systems, government policies must be restructured (Alam, 2022;Rehman and Islam, 2022;Xia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies prove a strong positive connection between business and the overall environment. As FDI is more inclined toward investment in less efficient entry and exit systems, government policies must be restructured (Alam, 2022;Rehman and Islam, 2022;Xia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In recent literature, a growing amount of research and discussion has been devoted to determining whether or not there is a connection between the responsible and socially sustainable conduct of businesses and their financial performance in the long run (Lassala et al, 2017;Ganlin et al, 2021;Alam, 2022). Due to the extensive globalization that markets have undergone and the growing demand of stakeholders for social commitment and transparency from businesses, social, environmental, and economic actions with sustainability criteria have been implemented (Adams, 2002;Moneva & Eduardo, 2008).…”
mentioning
confidence: 99%
“…However, trade openness and foreign aid helped to reduce emissions. Alam (2022) investigated and also found that trade helped reduce CO 2 emissions in Oman during 1980-2020. Moreover, Joshua and Bekun (2020) investigated South Africa from 1970 to 2017 and found that total natural resources rents showed a significant contribution to pollutant emissions.…”
Section: Literature Reviewmentioning
confidence: 99%